2018
DOI: 10.1021/acsbiomaterials.8b00521
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ε-caprolactone)/Hydroxyapatite 3D Honeycomb Scaffolds for a Cellular Microenvironment Adapted to Maxillofacial Bone Reconstruction

Abstract: The elaboration of biomimetic materials inspired from the specific structure of native bone is one the main goal of tissue engineering approaches. To offer the most appropriate environment for bone reconstruction, we combined electrospinning and electrospraying to elaborate an innovative scaffold composed of alternating layers of polycaprolactone (PCL) and hydroxyapatite (HA). In our approach, the electrospun PCL was shaped into a honeycomb-like structure with an inner diameter of 160 μm, capable of providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…In the present study, we first confirmed the in vitro cytocompatibility of this honeycomb PCL-nHA scaffold seeded with rat BM-MSCs by analyzing cell attachment, cell morphology, and spatial distribution. The cells completely covered the honeycomb PCL-nHA scaffold, and so there was no preference for a particular part of the honeycomb structure; this has previously been observed with C3H10T1/2 cells after 48 h of culture (Garcia Garcia et al, 2018). This complete coverage could be explained by the honeycomb pattern's promotion of extracellular matrix synthesis and upregulation of type II collagen (Eniwumide et al, 2014).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In the present study, we first confirmed the in vitro cytocompatibility of this honeycomb PCL-nHA scaffold seeded with rat BM-MSCs by analyzing cell attachment, cell morphology, and spatial distribution. The cells completely covered the honeycomb PCL-nHA scaffold, and so there was no preference for a particular part of the honeycomb structure; this has previously been observed with C3H10T1/2 cells after 48 h of culture (Garcia Garcia et al, 2018). This complete coverage could be explained by the honeycomb pattern's promotion of extracellular matrix synthesis and upregulation of type II collagen (Eniwumide et al, 2014).…”
Section: Discussionsupporting
confidence: 53%
“…In the present study, the μCT parameters did prevent us from detecting the honeycomb PCL-nHA scaffold and thus from evaluating its rate of degradation over time. However, given that the mean ± SEM thickness of our honeycomb PCL-nHA scaffold was 31 ± 5 μm (Garcia Garcia et al, 2018), we can assume that it did not fill the bone defect (500 μm in thickness). Hence, the scaffold left space for bone synthesis, which might have contributed to the rapid bone construction (with a bone volume fraction of more than 80% after 8 weeks) relative to most of the scaffolds tested in the same model (Chamieh et al, 2016;Chen et al, 2019;Orbay et al, 2017;Son, Linh, Yang, & Lee, 2013;Wang et al, 2019;Wu et al, 2019;Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A) Organotype culture of cells from a chicken bone embryo onto a honeycomb PCL/hydroxyapatite ELS scaffold produced by electrospinning/electrospraying onto a micropatterned collector. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: From Nanoparticles and Polymers As Building Blocks To Smart mentioning
confidence: 99%